2013
DOI: 10.1615/jenvironpatholtoxicoloncol.2013007074
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Pu-erh Tea Increases In Vitro Anticancer Activities in HT-29 Cells and Has Antiangiogenetic Effects on HUVECs

Abstract: Pu-erh tea is produced in China and known to possess medicinal properties. The anticancer and antiangiogenesis effects of fermented Pu-erh tea on HT-29 colon cancer cells and human umbilical vein endothelial cells, respectively, were examined. Two kinds of unfermented and fermented Pu-erh tea (Seven-son tea cake Pu-erh tea and Xiaguan bowl tea [X]) and green tea were used. An MTT assay showed fermented Pu-erh tea X (85% inhibition) possessed more potent anticancer activities than unfermented Pu-erh tea X (67% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Kim et al (26) demonstrated that kaempferol can modulate angiogenesis and immune-endothelial cell adhesion. Zhao et al (27) showed that kaempferol from Pu-erh tea has anti-cancer and anti-angiogenesis effects. Currently, the mechanism involved in the kaempferol anti-angiogenesis effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (26) demonstrated that kaempferol can modulate angiogenesis and immune-endothelial cell adhesion. Zhao et al (27) showed that kaempferol from Pu-erh tea has anti-cancer and anti-angiogenesis effects. Currently, the mechanism involved in the kaempferol anti-angiogenesis effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The same extract showed antiangiogenetic effects on HUVECs and anticancer activity on HT-29 cells [78] . Such evidences suggest a positive effect of food fermentation on endothelial progenitors number and functions.…”
Section: Fermented Food: a New Class Of Nutraceuticals?mentioning
confidence: 85%
“…The Bcl-2 family, which includes promoters (Bax and Bid) and inhibitors (Bcl-2 and Bcl-xL), is a key regulator in mitochondria-mediated apoptosis (21). In the present study, the gene and protein expression of Bax was increased, whereas the protein expression of Bcl-2 was decreased following treatment with D. candidum .…”
Section: Discussionmentioning
confidence: 99%